2021
DOI: 10.1002/hed.26736
|View full text |Cite
|
Sign up to set email alerts
|

High rates of postoperative radiotherapy delay in head and neck cancer before and after Medicaid expansion

Abstract: Background The objective is to study the effect of Medicaid expansion on postoperative radiation therapy (PORT) delay in patients with head and neck squamous cell carcinoma (HNSCC). Methods Patients from the National Cancer Database with HNSCC undergoing curative‐intent surgery in the 2 years before and after Medicaid expansion were analyzed (n = 11 717) using the difference‐in‐differences technique to study the effect on PORT delay. Results The rate of PORT delay before and after expansion was 66.0% and 66.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For the studies that described an intervention to reduce PORT delay, only data from the preintervention cohort were included in the meta‐analysis. Of the 25 studies that reported frequency of PORT delay defined at >6 weeks, the following were excluded from meta‐analysis: 10 were excluded to minimize duplication of patients included in the NCDB, 6,7,17,33‐39 and 1 was excluded for including a heterogeneous patient population and providing insufficient details about PORT 40 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the studies that described an intervention to reduce PORT delay, only data from the preintervention cohort were included in the meta‐analysis. Of the 25 studies that reported frequency of PORT delay defined at >6 weeks, the following were excluded from meta‐analysis: 10 were excluded to minimize duplication of patients included in the NCDB, 6,7,17,33‐39 and 1 was excluded for including a heterogeneous patient population and providing insufficient details about PORT 40 …”
Section: Methodsmentioning
confidence: 99%
“…Of the 25 studies that reported frequency of PORT delay defined at >6 weeks, the following were excluded from meta-analysis: 10 were excluded to minimize duplication of patients included in the NCDB, 6,7,17,[33][34][35][36][37][38][39] and 1 was excluded for including a heterogeneous patient population and providing insufficient details about PORT. 40…”
Section: Study Selection For Meta-analysismentioning
confidence: 99%
“…Medicaid patients were found to have more frequent delay of postoperative radiation than private insurance patients both before and after Medicaid expansion with no appreciable change with expansion (77% vs. 60% rate of delayed radiation in Medicaid vs. private, respectively). 79 The authors' main conclusion was that Medicaid expansion alone did not decrease radiation delay.…”
Section: Role Of Medicaid Expansionmentioning
confidence: 97%
“… 78 Unfortunately, over 60% of head and neck patients undergoing curative intent surgery do not receive their radiation within 6 weeks. 55 , 79 …”
Section: Role Of Medicaid Expansionmentioning
confidence: 99%